Heavy metals in neuston from the straits of Malacca. - Rezai, Hamid; Md. Yusoff, Fatimah (2011)
Heavy metals cadmium, lead, copper and zinc in neuston were analyzed from samples collected with a modified neuston net (310 μm mesh size) during an oceanographic cruise from July 29 to August 8, 2000 in the Straits of Malacca. The period of sampling coincided with South-West (SW) monsoon. The heavy metal concentrations in neuston were relatively low: ranging from 1.19-1013.70 μg g-1 wet weight for copper, 16.54-235.78 μg g-1 wet weight for zinc, 3.92-36.08 μg g-1 wet weight for lead and from 0.32-4.09 μg g-1 wet weight for cadmium. The heavy metal concentrations in neuston in this study were within the ranges published elsewhere, except for cadmium, there were significant differences (p <0.05) in concentrations of Cu, Pb and Zn between northern, central and southern parts of the Straits. However, concentrations of Cu and Zn were significantly (p <0.05) higher in near-coastal than offshore or neritic areas, whereas those of Pb and particularly Cd were higher in offshore areas though not significantly (p>0.05). The presence of two groups of stations with high and low heavy metal concentration as revealed by multivariate analyses corresponded mostly to near-coastal and neritic waters, respectively.